PREPARING THE ASEAN ECONOMIC COMMUNITY (MEA) WITH THE DEVELOPMENT STRATEGY OF SMALL AND MEDIUM ENTERPRISES (UMKM) TO GET BUSINESS CREDIT IN KELURAHAN CIBADUYUT BANDUNG - Dewi Untari; Dewi Endah Fajariana; Muchamad Ridwan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
From the results of interviews and preliminary observations that the development of Small and Medium Enterprises is essentially a shared responsibility between the government and society. In order to support the empowerment and development of Micro, Small and Medium Enterprises, especially in encouraging the distribution of credit to Micro, Small and Medium Enterprises in Cibaduyut Urban Village, for the development of Micro, Small and Medium Enterprises in Cibaduyut Village, Bandung, the strategies included in the first Bank Partner Financial Consultants in fostering and mentoring Micro Small Enterprises and Medium prospects who apply for business loans; second, socializing profit sharing or venture capital financing; third Increasing the participation of credit guarantee institutions for Micro, Small and Medium Enterprises and prospects who are faced with collateral requirements. It is expected that with the implementation of the above strategies, Micro, Small and Medium Enterprises will no longer experience difficulties in the submission of business capital loans from Credit Distribution Agencies. From each solution above, it is building and mentoring Micro and Small and Medium Enterprises, prospects who will apply for business loans. The results of the study showed that the community in the Cibaduyut Village with the optimization of the role of the Bank Partner Financial Consultant (KKMB), the requirements and procedures established by the credit channeling institutions, were no longer an obstacle for Micro and Small Businesses in obtaining business capital loans. The success of this approach will be seen from the increasing number of bankable Micro, Small and Medium Enterprises and obtaining business capital loans, and having a Bank Partner Financial Consultant (KKMB) operating on a business (mutually beneficial) basis so that it can finance itself.